Classes of developmental trajectories of body mass index: Differences in motor competence and cardiorespiratory fitness. Issue 6 (18th March 2020) - Lopes, Vitor P.; Utesch, Till; Rodrigues, Luis P.
ABSTRACT: The purpose was to identify classes of different developmental trajectories of BMI and testing them for differences in motor competence (MC) and cardiorespiratory fitness (CRF), in children and adolescents (4 to 13 years of age). This was a 5 years' longitudinal study with six cohorts. One hundred and forty-seven children (69 girls) divided into six cohorts participated. At baseline, the youngest and the oldest cohorts had 4 and 11 years of age, respectively. Height and weight were assessed, and BMI was calculated. MC was assessed with KTK and TGMD-2, and CRF was assessed with one-mile run/walk. Developmental trajectories of BMI were identified using latent class linear-mixed modelling. Latent class membership was explained according to covariates of MC and CRF. Two meaningful classes were identified. Class 1 (78.92% of the participants) showed lower initial BMI and a lower slope compared to class 2 (21.08% of the participants) (all ps < 0.001). Class membership only predicted trajectories in motor coordination, with children in class 1 having a better development. In conclusion, this study identified two meaningful trajectories for children based on their BMI development across five time points. In line with previous research, children with slower increasing BMI showed better motor coordination improvements.